Public Sector Employment Regimes Transformations of the State as an Employer - Gottschall, Karin; Kittel, Bernhard; Briken, Kendra; Heuer, Jan-Ocko.; Hils, Sylvia; Streb, Sebastian; Tepe, Markus; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book explores the extent to which a transformation of public employment regimes has taken place in four Western countries, and the factors influencing the pathways of reform. It demonstrates how public employment regimes have unravelled in different domains of public service, contesting the idea that the state remains a 'model' employer.
Keywords: Political science; Political economy; Comparative politics; Public policy; Social policy; Industrial sociology; Political Science and International Relations; Comparative Politics; Public Policy; Social Policy; Sociology of Work; Political Science; Political Economy; Electronic books